Methodology of Social Research ? Orthodoxy and Reflectivity - Malewski, Mieczysław (INSTED: Interdisciplinary Studies in Education & Society, 2012)
Within the last quarter of the century social sciences have been witnessing a quiet methodological revolution. The noticed expansion of interpretative approaches and the growing popularity of quality research may be perceived as a form of academic rebellion against the omnipotent scientistic doctrine with its guaranteed monopoly for setting methodological standards. The movement of quality researchers, particularly in its radical and critical version, undermines a thesis that recognised methodological standards reflect universal rules of the cognitive reason. In this approach the methods of science are a collection of conventions negotiated within reserachers? communities and social and cultural provenance.